2018
DOI: 10.26719/2018.24.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness and acceptability of anti-HPV vaccine in the Arab states of the Middle East and North Africa Region: a systematic review

Abstract: An examination of the region collectively offers an insight into the willingness of the general population and healthcare providers to receive more information about the virus and prevention of infection through vaccination. This review suggests that the vaccine acceptability would be high once cost concerns are resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 15 publications
1
32
1
Order By: Relevance
“…The level of the knowledge also varies among different populations. The knowledge range tends to be lower in men (31%) than in women (31-65%), whereas that among adolescents is at 20.0%, which needs to be improved urgently (Gamaoun, 2018). A study in Urumqi, China (Tian et al, 2019), showed that local residents have a better understanding of HPV knowledge compared with non-local residents, most of whom came from rural or county towns around Urumqi.…”
Section: Discussionmentioning
confidence: 99%
“…The level of the knowledge also varies among different populations. The knowledge range tends to be lower in men (31%) than in women (31-65%), whereas that among adolescents is at 20.0%, which needs to be improved urgently (Gamaoun, 2018). A study in Urumqi, China (Tian et al, 2019), showed that local residents have a better understanding of HPV knowledge compared with non-local residents, most of whom came from rural or county towns around Urumqi.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, raising awareness among the general population as well as among specific high-risk subpopulations is considered the most effective method to prevent HPV infection. This requires active involvement by the physicians, and specifically the obstetric gynecology, family medicine and primary health care physicians, to promote the vaccine and other preventive measures among the community [21, 22]. However, inadequate knowledge and awareness among physicians about the importance of the HPV vaccine was highlighted as one of the major limitations to successful vaccination programs [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…In the study populations included in this analysis, a high level of acceptance of the HPV vaccine was observed among people living with HIV, as has been found in other studies. [28][29][30][31][32][33][34][35][36][37][38][39] A number of studies have also found that high HPV vaccine acceptability in men who have sex with men (with or without HIV) was 75%. 33,46 As for women, in a cohort of young female sex workers living with HIV, 100% agreed to apply the first dose of vaccine, while 79% completed the 3-dose schedule.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] In low-and middleincome countries diverse groups, including parents of adolescents and MSM, have shown moderate to high HPV vaccine acceptability. [33][34][35][36][37] Health education and vaccine promotion that is considered understandable, pertinent and that addresses rumors or incorrect information as well as social mobilization supporting HPV vaccine implementation are important factors related to HPV vaccine acceptability in low and middle-income countries. [38][39][40][41] Worldwide, healthcare provider recommendation is one of the most important facilitators of HPV vaccine acceptability and uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation